Patristic Exegesis The Myth of the Alexandrian-Antiochene Schools of Interpretation - Slade, Darren M. (2019)
The notion that there existed a distinction between so-called “Alexandrian” and “Antiochene” exegesis in the ancient church has become a common assumption among theologians. The typical belief is that Alexandria promoted an allegorical reading of Scripture, whereas Antioch endorsed a literal approach. However, church historians have long since recognized that this distinction is neither wholly accurate nor helpful to understanding ancient Christian hermeneutics. Indeed, neither school of interpretation sanctioned the practice of just one exegetical method. Rather, both Alexandrian and Antiochene theologians were expedient hermeneuts, meaning they utilized whichever exegetical practice (allegory, typology, literal, historical) that would supply them with their desired theology or interpretive conclusion. The difference between Alexandria and Antioch was not exegetical; it was theological. In other words, it was their respective theological paradigms that dictated their exegetical practices, allowing them to utilize whichever hermeneutical method was most expedient for their theological purposes. Ultimately, neither Alexandrian nor Antiochene exegetes possessed a greater respect for the biblical text over the other, nor did they adhere to modern-day historical-grammatical hermeneutics as theologians would like to believe.